# What is the standard form of y= (x-14)(x-2) ?

May 2, 2017

$y = {x}^{2} - 16 x + 28$

#### Explanation:

To find the standard form from this form (factored form), we simply multiply the sets of brackets. If you're unsure how to do that, see this link

$y = \left(x - 14\right) \left(x - 2\right)$
$y = {x}^{2} - 14 x - 2 x + 28$
Then collect the x terms, to get:
$y = {x}^{2} - 16 x + 28$

May 2, 2017

See the entire solution process below:

#### Explanation:

To get to the standard form of the equation you must multiply the two terms on the right side of the equation:

To multiply these two terms you multiply each individual term in the left parenthesis by each individual term in the right parenthesis.

$y = \left(\textcolor{red}{x} - \textcolor{red}{14}\right) \left(\textcolor{b l u e}{x} - \textcolor{b l u e}{2}\right)$ becomes:

$y = \left(\textcolor{red}{x} \times \textcolor{b l u e}{x}\right) - \left(\textcolor{red}{x} \times \textcolor{b l u e}{2}\right) - \left(\textcolor{red}{14} \times \textcolor{b l u e}{x}\right) + \left(\textcolor{red}{14} \times \textcolor{b l u e}{2}\right)$

$y = {x}^{2} - 2 x - 14 x + 28$

We can now combine like terms:

$y = {x}^{2} + \left(- 2 - 14\right) x + 28$

$y = {x}^{2} + \left(- 16\right) x + 28$

$y = {x}^{2} - 16 x + 28$